1995
DOI: 10.1111/j.1365-2338.1995.tb01441.x
|View full text |Cite
|
Sign up to set email alerts
|

Isozyme analysis for characterization of Ganoderma strains from south‐east Asia 1

Abstract: Extracellular pectinase isozymes were determined by polyacrylamide gel electrophoresis (PAGE) for isolates of Ganoderma collected from a range of hosts and environments in south‐east Asia. Findings indicate these techniques to be of use in the differentiation of strains isolated from different hosts and environments. Average linkage cluster analysis of pectinase isozyme banding patterns separated isolates according to host of origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…This presence of the specific band in saprobic isolates from coconut and areca palms would suggest that these isolates are either the same taxon as the oil-palm pathogen, or are very closely related to it. This is in agreement with previous observations and molecular studies which have suggested that BSR of oil palm may be caused by isolates saprobic on other palm hosts (Miller, 1995;Miller et al, 1995). The absence of the band in the saprobic isolates from poisoned oil palm suggests that not all saprobic Ganoderma on palms belong to the BSR taxon.…”
Section: Evaluation Of Primer Combinationsupporting
confidence: 92%
See 2 more Smart Citations
“…This presence of the specific band in saprobic isolates from coconut and areca palms would suggest that these isolates are either the same taxon as the oil-palm pathogen, or are very closely related to it. This is in agreement with previous observations and molecular studies which have suggested that BSR of oil palm may be caused by isolates saprobic on other palm hosts (Miller, 1995;Miller et al, 1995). The absence of the band in the saprobic isolates from poisoned oil palm suggests that not all saprobic Ganoderma on palms belong to the BSR taxon.…”
Section: Evaluation Of Primer Combinationsupporting
confidence: 92%
“…Several molecular approaches have been used to characterize isolates of Ganoderma (Miller, 1995;Miller et al, 1995;Abu-Seman et al, 1996;Gottlieb et al, 1998). The most widely used has been isoenzyme analysis and this has given rather variable results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although either vegetation could have supported Ganoderma populations, variation in strains adapted to palms is more likely to have originated in native palm infections. Evidence of such an origin was found previously (Miller et al, 1995a), with isolates from palmaceous and nonpalmaceous hosts separating on the basis of extracellular pectinase zymograms. Oil palm is propagated as seed from crosses between cultivars Dura and Pisifera, so that an oil palm stand is not a genetically homogeneous host.…”
Section: Discussionmentioning
confidence: 77%
“…The molecular systematics of macrofungi has been studied by various methods using DNA-DNA hybridization, restriction enzyme analysis - RFLP, rDNA, mtDNA and sequencing analysis of ITS 27 . Pectinase isoenzyme 36 , manganese superoxide dismutase 37 , 38 , ITS and 25S ribosomal sequences 34 , 35 , 39 were used to construct molecular phylogeny in macrofungal species. Later, ITS was used as a DNA barcode for fungal identification 32 , 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%